Towards a more natural governance of earth’s biodiversity and resources - Macdonald, D; Johnson, D; Whitehouse, H (Medknow Publications, 2019)
Humans, like other animals, have aptitudes and limitations shaped by natural selection; knowledge of these—along with that of how mammals, including people, form societies and cooperate—can be fruitfully applied to the challenge of biodiversity conservation. Here, we outline the natural principles that might help conservationists (and indeed any other group concerned with political problems) get the best outcomes by aligning efforts with the grain of nature, rather than against it; we call this approach ‘Natural Governance’. We illustrate the value of this perspective with reference to two aspects of conservation strategy—rethinking the spatial scales at which it is effective to plan conservation and energising human society to care enough to enable it. A Natural Governance approach stands on three critical pillars: (1) ecology (the dynamic balance between organisms and their environment), (2) cooperation (adaptations to act collectively even where this incurs short-term costs to self-interest), and (3) cultural systems (how these adaptations are manifested and vary across societies). It is commonly assumed that human society stems purely from political or socially-constructed influences. The biological perspective does not say that these influences are unimportant, but it reveals viewing humanity out of the evolutionary context to be a cripplingly narrow picture